PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN MODERASI BUDAYA ORGANISASI (Studi Kasus Pada Guru SD Negeri Gugus Nyi Ageng Maloka Kecamatan Lasem Kabupaten Rembang) - Khofsah, 12.52.02.0205 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze that moderate the organizational culture of work discipline and motivation to work on the performance of primary school teachers Nyi Ageng Maloka Force District of LasemApexdistrict. Respondents in this study is a population of teachers working in elementary schools in District of Lasem Rembang totaling 69 people. Mechanical testing of the data used in this study include testing the validity of the factor analysis, reliability testing with Cronbach alpha formula, multiple regression analysis, and the significance test, the coefficient of determination to prove the truth of the researchhypothesis The results showed that; labor discipline does not affect the performance of teachers, motivation positive and significant impact on teacher performance, organizational culture positive and significant impact on teacher performance, organizational culture does not moderate influence on the performance of teachers work discipline, organizational culture does not moderate influence on the performance of teachers work motivation on Elementary School Cluster Nyi AgengMalokaDistrictofLasemRembang. Keywords : work discipline, motivation, organizational culture, teacher performance